Design and implementation of web-based aphid (Lipaphis erysimi) forecast system for oilseed Brassicas - Kumar, Vinod; Kumar, Amrender; Chattopadhyay, Chirantan (The Indian Journal of Agricultural Sciences, 2012)
Oilseed Brassicas are major crops in India and world over. Keeping in view severe losses caused by aphid (Lipaphis erysimi) in these crops, efforts were initiated to devise user-friendly web-based software for forecasting their occurrence. Multiple stepwise regressions have been followed for developing aphid prediction models in practice. Interpretation and use of these models was difficult for any person not having proper statistical knowledge. Further, keeping in view the need of online software tool to help the plant researchers, extension personnel and farmers in forecasting of aphid infestation and timely application of control measures, the study was carried out. This paper introduces design and implementation of web-based forecast software for prediction of aphid on oilseed Brassicas in India. The software uses statistical prediction models developed based on weather parameters as independent variables and crop age at time of first appearance of aphid on crop, peak number of aphid and crop age at peak population as dependent variables, which were fitted by multiple stepwise regressions. The software has been developed by deploying ubiquitous unbeatable open sources technology. The system provides a prediction of mustard aphid infestation well in advance of their actual arrival on the crop along with recommendations for need-based insecticide application.